Local structure investigation and properties of Mn-doped BiFeO3–BaTiO3 ceramics. Issue 3 (April 2015) - Unruan, S.; Srilomsak, S.; Priya, S.; Jantaratana, P.; Rujirawat, S.; Yimnirun, R.
Abstract: Bi0.75 Ba0.25 (Fe, Ti)1− x Mn x O3 with x =0, 3 and 5 mol% Mn ceramics were prepared by a solid state reaction method. The relationships between site substitution of Mn in Mn-doped 0.75BF–0.25BT ceramics, phase formation and their properties were investigated. The addition of Mn was shown to improve densification, electrical and magnetic properties, especially ME coefficient. The Synchrotron X-Ray Absorption Near Edge Structure (XANES) spectra showed that Mn substituted for Fe/Ti atom and did not affect the oxidation state of Ti and Bi. However, a significant change of oxidation state was observed in Fe, Mn and Ba atoms.